GOVERNMENT STRATEGY AND POLICY IN SOCIAL CONFLICT RESOLUTION IN LUWU AND NORTH LUWU REGENCIES, SOUTH SULAWESI PROVINCE, INDONESIA - Sangkala; Atmansyah, Lutfi; Hans, Amril Hans (LPPM-STPI, 2021)
Research on Government Strategy in Social Conflict Resolution in Luwu and North Luwu Districts of South Sulawesi Province is a study that is intended to find out why the strategies and policies for resolving social conflicts that have occurred have not been able to be resolved completely by the local government. In terms of the government's duty to guarantee the creation of security in the community. Therefore, it is important to do research to reveal what is the cause. To find answers to these problems, further research problems are formulated, namely, what causes social conflict to occur, how the efforts and stages of conflict resolution are carried out by the government, what are the inhibiting factors so that conflicts are often repeated, and what strategies and policies are used in resolving conflict.